(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Micro Small and Medium Enterprises (MSMEs) sector has played a significant role to develops the economy. This sector has always been considered essential driver of economic process. This sector has proposed as ‘Engines of growth’ (Virk & Negi, 2019). This sector of Tripura has been contributing to the economic development of the state. This present paper is an attempt to understand the overview of the MSME sector of Tripura. For this study, analytical research has used and secondary data is collected from Annual Report of MSME, central and state government published report from the Financial Year (FY) 2007- 08 to 2019-20. This study also followed by the traditional dimensions such as; trends and growth rate of MSME units, employment and investment by the government to this sector. In addition, the measure of Growth Rate (GR) for all dimensions; the Compound Annual Growth Rate (CAGR) and percentage methods are used. The findings of this study revealed the trends and growth rate of MSME units and employment generation are recorded fluctuating in different years and the investment growth rate by the government to the MSME sector has also fluctuated within the period under study.